Analysis of tool deformation effects on the precision of miniature metallic part - Tan, Agnes Wei Lin (2011)
Product miniaturisation has gained much attention with wider applications over the recent years. Together, micro-forming, which is used for fabricating miniature metallic parts, is being concerned for better utilisation. One of the considerations for micro-forming to look into is the consequences of high forces present on the tools used during the process, which can cause tool elastic deflection and influence the final dimensions of the formed parts. In this project, useful results for the deformation history of the process were obtained through the simulations, which could be applied to predict the influence of tool elastic deflection during micro-forming of miniature metallic part.